Assessing publication rates from medical students' mandatory research projects in the Netherlands: a follow-up study of 10 cohorts of medical students. Issue 4 (4th April 2022) - den Bakker, Charlotte R; Ommering, Belinda WC; van Leeuwen, Thed N; Dekker, Friedo W; De Beaufort, Arnout Jan
Abstract : Objectives: The medical field is facing a clinician-scientist shortage. Medical schools could foster the clinician-scientist workforce by offering students research opportunities. Most medical schools offer elective research programmes. Subsequently, a subset of doctors graduates without any research experience. Mandatory research projects may be more sufficient to develop clinician-scientist, but take more supervision and curricular time. There is limited insight in the scientific outcomes of mandatory research experiences. This study aims to examine publication rates of a mandatory research experience, identify factors associated with publication, and includes postgraduate research engagement. Design and setting: Prospective follow-up study involving 10 cohorts of medical students' mandatory research projects from Leiden University Medical Center. Participants: All medical students who conducted their research project between 2008 and 2018 (n=2329) were included. Main outcome measure: Publication rates were defined as peer-reviewed scientific publications, including research papers, reviews, and published meeting abstracts. Postgraduate research engagement was defined as research participation and dissemination of research at scientific conferences or in journals. Results: In total, 644 (27.7%) of all mandatory research experiences resulted in publication, with students mainly as first (n=984, 42.5%) or second author (n=587, 25.3%) and above world average citation impact (mean normalised journal score 1.29, mean normalised citation score 1.23). Students who conducted their research in an academic centre (adjusted OR 2.82; 95% CI 2.10 to 3.77), extended their research (adjusted OR 1.73; 95% CI 1.35 to 2.20), were involved in an excellency track (adjusted OR 2.08; 95% CI 1.44 to 3.01), or conducted clinical (adjusted OR 2.08; 95% CI 1.15 to 3.74) or laboratory (adjusted OR 2.16; 95% CI 1.16 to 4.01) research published their research more often. Later as junior doctors, this group significantly more often disseminate their research results at scientific conferences (adjusted OR 1.89; 95% CI 1.11 to 3.23) or in journals (adjusted OR 1.98; 95% CI 1.14 to 3.43). Conclusions: Our findings suggest that a significant subset of hands-on mandatory research projects with flexible learning pathways result in tangible research output with proper impact and that such successful experiences can be considered as diving board towards a research-oriented career.